PROCESS OF MANAGING INCOMING AND OUTGOING LETTER IN BAPPEDA NAGAN RAYA REGENCY - Ratna Dewi; Muzakir Muzakir (Jurnal Ilmiah Teunuleh, 2021)
This study aims to determine how the process of managing incoming and outgoing letters at the Nagan Raya Bappeda Office. This study uses a qualitative descriptive method that draws whatever happens in the field without changing it. This study uses primary data and secondary data. Primary data were obtained from interviews with Bappeda Nagan Raya employees. While secondary data obtained from the web. Respondents from this study were 5 Bappeda employees. The results of this study indicate that the process of managing incoming and outgoing mail has not been carried out effectively. This is because the process of managing incoming and outgoing mail is still using manual procedures so that sometimes errors occur in the process.